Environmental Policy, Firm Location, And Product Differentiation: The Role of Green Preferences and Inter-firm Pollution - Michael Kuhn (Universität Rostock, Institut für Volkswirtschaftslehre, 1997)
Endogenous firm location is analyzed in a discrete two-region-two-firm model of product differentiation. In a non-cooperative game, two regional governments first decide on the imposition (or lifting) of domestic production standards; firms then choose technology (clean or polluting), location and price. Equilibrium quality and location structure are determined analytically. The existence of consumers willing to pay a premium on clean production methods, and the possibility of inter-firm pollution alleviate the tendency of firms to delocate into the region with the weaker regulation; then, a deregulatory race to the bottom is less likely.
Keywords: H73; L13; Q28; 330; environmental policy; product differentiation; firm location; institutional competi-tion; green preferences; Umweltpolitik; Standortwettbewerb; Standorttheorie; Produktdifferenzierung; Duopol; Spieltheorie; Umweltbewusstsein; Willingness to pay; Theorie